Manichaeism in Central Asia and China - Lieu, Samuel (Nag Hammadi and Manichaean Studies, 1998)
The discovery of genuine Manichaean texts from sites like Turfan and Tun-huang since the beginning of the century has greatly increased our knowledge of the teaching of Manichaeism and of its amazing geographical spread in pre-Islamic times. This volume brings together the contributions by a leading authority on the subject including a long survey article on the history of the discovery of the texts from Central Asia as well as articles focusing on some of these texts and on the incredible history of adaptation and survival of the sect in China proper. The studies include many Chinese texts on Manichaeism made available for the first time in their original scripts and in translation. The volume also contains the first ever working catalogue of all Manichaean texts (in western as well as oriental languages) published up to 1997.